Epigenetic Modulation on Tau Phosphorylation in Alzheimer’s Disease - Chao-Chao Yu; Tao Jiang; Ao-Fei Yang; Yan-Jun Du; Miao Wu; Li-Hong Kong (Neural Plasticity)
Tau hyperphosphorylation is a typical pathological change in Alzheimer’s disease (AD) and is involved in the early onset and progression of AD. Epigenetic modification refers to heritable alterations in gene expression that are not caused by direct changes in the DNA sequence of the gene. Epigenetic modifications, such as noncoding RNA regulation, DNA methylation, and histone modification, can directly or indirectly affect the regulation of tau phosphorylation, thereby participating in AD development and progression. This review summarizes the current research progress on the mechanisms of epigenetic modification associated with tau phosphorylation.